Global trends in research related to ecotourism: A bibliometric analysis from 2012 to 2022 - Zhi Jin; Ming Gao (SAGE Open)
This study aims to analyze the current state, research hot spots and research trends of ecotourism research. We searched document data on ecotourism from the Web of Science core collection database and retrieved 2,998 articles from 2012 to 2022. CiteSpace, Bibliometrix, and VOSviewer software were utilized to visualize the countries, institutions, authors, research hotspots and trends of ecotourism research. The number of ecotourism-related articles published annually has increased significantly. The United States leads other countries in the number of publications, followed by China and Australia. The analysis of keywords co-occurrence shows that nature conservation, residents’ interests, tourists’ attitudes and behaviors, and sustainable management are the current research hot spots of ecotourism research. The timeline view of the reference co-citation analysis indicated that motivation, ecotourism cognition, social media, COVID-19, and destination social responsibility represent the emerging frontiers in the research of ecotourism. This bibliometric study provides the current status and trends in the research of ecotourism, which may offer some guidance for more extensive and in-depth ecotourism-related studies in the future.